Evaluation of new volatile compounds as lures for western flower thrips and onion thrips in New Zealand and Spain - Teulon, D.A.J.; Casta??, C.; Nielsen, M-C; El-Sayed, A.M.; Davidson, M.M.; Gardner-Gee, R.; Poulton, J.; Kean, A.M.; Hall, C.; Butler, R.C.; Sansom, C.E.; Suckling, D.M.; et al. (New Zealand Plant Protection, 2014)
Two glasshouse trials in a capsicum crop near Warkworth New Zealand in January 2011 and two field trials in a nectarine orchard near Lleida Spain in July 2013 were undertaken to determine if trap capture of Frankliniella occidentalis (western flower thrips WFT) and Thrips tabaci (onion thrips OT) could be increased by alternative volatile compounds beyond the known thrips attractant methyl isonicotinate (MI) On blue sticky board traps in the crop in New Zealand none of six alternative compounds tested caught more thrips (mostly WFT OT and two other species) than the Control traps In contrast to MI catches with the alternative lures were mostly significantly lower For both trials in the orchard in Spain using white water traps the highest numbers of WFT and OT were caught higher than most of the nine alternative odour compounds tested